The Effectiveness of the Law in the Protection of Mountain Gorillas ( A Case Study on Bwindi Impenetrable National Park) - Prudence Persey Guma (Uganda Christian University, 2025)
This dissertation critically examines the effectiveness of the legal framework in the protection and conservation of mountain gorillas in Bwindi impenetrable national park, Uganda. It explores how domestic, regional and international legal instruments and policies contribute to gorilla conservation with a particular focus on Uganda’s policy developments . This dissertation evaluates the strengths and weaknesses of key instruments like the Uganda wildlife policy 2014,the Uganda Wildlife act as revised , the national environmental act as revised and the 1995 constitution of the republic of Uganda as amended while integrating doctrines like the public trust doctrine, environmental social impact assessment and community participation principles. It also assesses the role of regional protocols such as the East African Community Treaty (EAC) And International Instruments like the Convention on Biological Diversity(CBD).By analyzing the different instruments in the protection of mountain gorillas, this study also proposes recommendations for a more inclusive and adaptive frame work that enhances the protection of endangered species.